Immune checkpoint molecules as biomarkers of Staphylococcus aureus bone infection and clinical outcome - Motoo Saito; Katya A. McDonald; Alex K. Grier; Himanshu Meghwani; Javier Rangel-Moreno; H. Mark Kenney; Enrique Becerril-Villanueva; Armando Gamboa-Dominguez; Jennifer Bruno; Christopher A. Beck; Richard A. Proctor; Stephen L. Kates; et al. (Communications Medicine, 2026)
Abstract Background Staphylococcus aureus prosthetic joint infections (PJIs) are broadly considered incurable, and clinical diagnostics that guide conservative vs. aggressive surgical treatments don’t exist. Understanding the human T cell response to chronic S. aureus osteomyelitis may lead to improved patient outcomes and inform new therapeutic strategies. Methods We performed multi-omics studies, including flow cytometry, scRNA-seq, and immunofluorescence in a humanized NSG-SGM3 BLT mouse model and with human clinical samples to characterize the human T cell landscape in S. aureus osteomyelitis. Results Human T cells are remarkably heterogeneous in gene expression and abundance. Notably, the CD4 Th1/Th17 cells comprise a mixed population of activated, progenitor-exhausted, and terminally-exhausted states with increased expression of immune checkpoint proteins (LAG-3, TIM-3). Importantly, these proteins are upregulated in the serum and the bone marrow of patients with S. aureus PJI. In a clinically informative pilot cohort, a multiparametric diagnostic integrating high serum immune checkpoint protein levels with low proinflammatory cytokine levels (IFN-γ, IL-2, TNF-α, IL-17) reveals that TIM-3 was highly predictive of adverse disease outcomes (AUC = 0.89). Conclusions T cell impairment, marked by immune checkpoint expression and exhaustion, could serve as a functional biomarker for S. aureus PJI disease outcome, and therapeutic blockade of checkpoint proteins may represent a potential strategy to improve outcomes following surgery.